Epidemiology and Molecular Aspect of pediculosis among Primary School Children in Sulaimani Province Kurdistan-Iraq - A. Haama, Abdullah (Kurdistan Journal of Applied Research, 2020)
Pediculosis is the term for head lice (Pediculus humanus capitis) and the other hairy parts infestation with any stages of lice. The lice is a human blood sucking ecto-parasite which can cause severe itching. Direct contact, Sharing of clothing and combs can be a way for lice transmission from infected person to another.This study had been done to determine the pediculosis infection rate and risk factors asociassion with head lice among primary schools children in Sulaimani Province, all cases were evaluated by physical examination (visual inspection) and detail structured questionnaire which was including education levels, family size, hair washing frequency, type and length of hair, mother occupation and education, father occupation, and education was used, the polymerase chain reaction (PCR) used for confirming the head lice clade. A total of 4087 students was inspected from 13 primary schools in Sulaimani city, with the overall prevalence of 8.3%, The participants were 2046 males and 2041 females with prevalence 2.20% and 6.1% respectively. The age of respondents was between 5-13 years. The prevalence was higher in large family members in comparing to those with small family members. The amplicons product from Polymarase chain Reaction was visualized on 1.5% agarose gel, and expected DNA band size of head lice's was approximately 486 bp which confirms that these lice's belong to the head lice group clade A . In conclusion the school aged children in Sulaimani province were suffering from peiculosis with high prevalence rate and it has a direct impact on children cognitive and school activity performance.